2008
DOI: 10.1093/molbev/msn126
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Genetic Instability: A Tumor-Permissive Mechanism for Maintaining the Evolvability of Higher Species through Methylation-Dependent Mutation of DNA Repair Genes in the Male Germ Line

Abstract: Tumor suppressor genes are classified by their somatic behavior either as caretakers (CTs) that maintain DNA integrity or as gatekeepers (GKs) that regulate cell survival, but the germ line role of these disease-related gene subgroups may differ. To test this hypothesis, we have used genomic data mining to compare the features of human CTs (n = 38), GKs (n = 36), DNA repair genes (n = 165), apoptosis genes (n = 622), and their orthologs. This analysis reveals that repair genes are numerically less common than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 147 publications
1
17
0
Order By: Relevance
“…For this reason alone, cancer treatment strategies focused solely on “driver” pathway inhibition seem likely to fail – for no sooner is the proverbial plug extracted from the driver pathway than the underlying apoptotic gene defect permits selection for heterologous pathway upregulation and/or additional oncogenic events, manifesting as a rapidly proliferative (high Ki67) tumor outgrowth reflecting the suppressor gene mutation burden (9). This problem is made even worse by coexisting caretaker defects that speed selection and cell adaptation – a useful coping mechanism for germline (species) evolution (10), but yet another therapeutic hurdle for restoring phenotypic stability to growing neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason alone, cancer treatment strategies focused solely on “driver” pathway inhibition seem likely to fail – for no sooner is the proverbial plug extracted from the driver pathway than the underlying apoptotic gene defect permits selection for heterologous pathway upregulation and/or additional oncogenic events, manifesting as a rapidly proliferative (high Ki67) tumor outgrowth reflecting the suppressor gene mutation burden (9). This problem is made even worse by coexisting caretaker defects that speed selection and cell adaptation – a useful coping mechanism for germline (species) evolution (10), but yet another therapeutic hurdle for restoring phenotypic stability to growing neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…69 Indeed, increasing evidence supports the importance of such epistatic processes for mammalian cancer development 24,[70][71][72][73] and, perhaps, also for transgenerational carcinogenesis. 6,74 The central finding of the present study is the unanticipated insight that the structural and functional attributes of GKs and POs-when compared with control subgroups of CT cancer suppressor genes and functionally unrelated but developmentally important HD genes-are strikingly similar, as indicated by congruences of evolutionary rate, expression level and breadth, gene length and methylation-dependent mutation confirmed by logistic regression and C-statistics. These data imply that GKs have undergone epigenetic evolution trajectories similar to those of POs, suggesting an explanation for the otherwise puzzling observation that wild-type GK (but not CT) expression is often selectively increased in tumors.…”
Section: Discussionmentioning
confidence: 64%
“…Framedependent dinucleotide alignment and evolutionary analysis have shown that CpG sites in GKs and POs fix missense mutations more often than do those in CTs, and that similar trends apply to wholegenome comparison of apoptosis vs repair genes. 6 As the minimum sequence motif is a dinucleotide, we hypothesized that nonrandom alterations in dinucleotide patterns-including asymmetries due to transcription-coupled repair-may be selected from transgenerational variations, the frequency of which varies with germline gene methylation. 58 With this in mind, directional analyses of methylation- Similarity of tumor suppressors and oncogenes Y Zhao and RJ Epstein dependent dinucleotides in the target gene sets reveal an asymmetry: not only are GKs and POs characterized by a higher CpG content than CTs but also by a selectively lower CpA-but not TpG-content, suggesting greater transcription-coupled repair of methylation-dependent mutation in GKs and POs than in CTs.…”
Section: Gene Length and Gc Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for a trade‐off between male fertility and cancer risk comes from studies the Y‐linked TSPY1 gene, which exhibits positive correlations of gene copy number with human male sperm count, 286 and aberrant high expression of the gene associated with a range of cancers 287 . More generally, mouse knockouts of tumor‐suppressor genes that are not lethal exhibit a striking preponderance of differential phenotypic effects on fertility, especially in males 288 …”
Section: The Genetic Axis Of Evilmentioning
confidence: 99%